SCIENTIFIC PRODUCTIVITY IN RELATION TO MOUTH NEOPLASMS AND MOUTH REHABILITATION: A BIBLIOMETRIC ANALYSIS - Marta Regina Chaves Camilo Fernandes; Carlos Roberto Lyra da Silva; Jully Hannay Santos de Souza; Larissa Chaves Morais de Lima; Isabel Cristina Ramos Vieira Santos; Inácia Sátiro Xavier de França (Universidade Federal do Paraná, 2017)
The objectives of this study were to analyze the results of articles retrieved on the subject of mouth neoplasms and mouth rehabilitation, published between 1990 and April 2016, identify the dispersion of the publications, and examine authorship patterns and citations in the Scopus database, based on the Laws of Bradford and Lotka. This was a bibliometric study, with a descriptive and quantitative approach. An analysis of articles published in journals indexed in the Scopus database was performed, using the terms "Mouth Neoplasms" and "Mouth Rehabilitation". Twenty-eight original articles were retrieved, published in 18 journals, with irregular distribution in the period studied. At the time of analysis, 222 citations were identified with a mean of eight per document. The fields of medicine and dentistry stood out with publications on the theme. Germany had the largest scientific production. The study revealed a modest number of publications and the need for nursing engagement in this area of research.